Pengaruh Likuiditas dan Struktur Modal terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi - Amelia Nabila Afra; Ira Hapsari; Fitriati, Azmi; Wibowo, Hariyanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the effect of liquidity and capital structure on firm value, with profitability serving as a moderating variable, in conventional banking institutions in Indonesia. The study employs secondary data obtained from the financial statements of 47 conventional banks listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period, resulting in a total of 168 observations. Panel data regression analysis is applied, supported by the Chow test and the Hausman test to determine the most appropriate estimation model. Based on the test results, the Fixed Effect Model (FEM) is selected and adjusted using robust standard errors to address heteroskedasticity and autocorrelation issues. The moderating role of profitability is examined using Moderated Regression Analysis (MRA). The findings indicate that liquidity and capital structure have a positive effect on firm value. However, profitability is found to weaken the relationship between liquidity and capital structure and firm value. These results suggest that as profitability increases, firms tend to rely more on internal financing, thereby reducing the sensitivity of firm value to liquidity and capital structure.